Efektivitas Media Games Book dalam Upaya Meningkatkan Pembelajaran Mengenal Anggota Tubuh Manusia Bagi Anak Tunagrahita Sedang - Vocia, Widari; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2022)
This research was raised based on the problem of a child with mental disabilities in class I / C not knowing human limbs. . Researchers used a media games book in introducing human limbs to children with mental disabilities in class I / C at SLB N 1 Kubung, Solok Regency. The tyype of research applied is experimental research in the form of Single Subject Research (SSR) with an A-B-A design. Data observation is carried out with deed test techniques and documentation using the data collection tool of the deed test instrument in the form of a checklist. In baseline conditions (A1) results were obtained 20%, 26%, 26%, intervention conditions (B) obtained results of 50%, 50%, 60%, 56%, 66%, 66%, 86%, 86%, 86%, and baseline conditions (A2) obtained results of 73%, 86%, 90%, 90%, 90%, 90%. Based on data analysis, the results of this study state that the use of media games books can improve the ability of children with mental disabilities to recognize human limbs.